Seasonal dynamics of extremely halophilic microbial communities in three Argentinian salterns - Di Meglio, Leonardo Gabriel (2016)
Seasonal sampling was carried out at three Argentinian salterns, Salitral Negro (SN), Colorada Grande (CG) and Guatraché (G), to analyze abiotic parameters and microbial diversity and dynamics. Microbial assemblages were correlated to environmental factors by statistical analyses. Principal component analysis of the environmental data grouped SN and CG samples separately from G samples owing to G's higher pH values and sulfate concentration. Differences in microbial assemblages were also found. Many archaeal sequences belonged to uncultured members of Haloquadratum and Haloquadratum-related genera, with different environmental optima. Notably, nearly half of the archaeal sequences were affiliated to the recently described ‘Candidatus Haloredividus’ (phylum Nanohaloarchaeota), not previously detected in salt-saturated environments. Most bacterial sequences belonged to Salinibacter representatives, while sequences affiliated to the recently described genus Spiribacter were also found. Seasonal analysis showed at least 40% of the microbiota from the three salterns was prevalent through the year, indicating they are well adapted to environmental fluctuations. On the other hand, a minority of archaeal and bacterial sequences were found to be seasonally distributed. Five viral morphotypes and also eukaryal predators were detected, suggesting different mechanisms for controlling prokaryotic numbers. Notably, Guatraché was the saltern that harbored the highest virus-to-cell ratios reported to date for hypersaline environments.